Análisis de la comunicación oral y no verbal en las personas que practican el acoso sexual callejero en los espacios públicos de la ciudad, para determinar el tipo de comunicación que estos generan en sus víctimas mujeres, estudiantes de los colegios Adolfo Valarezo y Beatriz Cueva de Ayora de la ciudad de Loja, edades comprendidas entre 15 y 17 años, periodo marzo – diciembre 2015. - Sanmartin Ochoa, Silvana Yamile (2016)
The current research work occurred as a necessity to take into account a problem that has not been given the proper attention required, the need to know what type of oral and non-verbal communication is generated in public spaces through street sexual harrasment and what are the repercussions had by its women victims, for which we took as a reference concepts and theoretical definitions which support the problematic of this research work. The delimitation of the problematic was given after the respective analysis of the contextualization and location, to study the topic of street sexual harassment with women students of 15, 16 and 17 years of age in the high schools Adolfo Valarezo and Beatriz Cueva de Ayora in the city of Loja, therefore we constructed the objectives, hypothesis, and justfication that serves to direct the process of investigation. In the actualization of this research work we employed the scientific method that through a qualitative analysis we used fundamental tools for the collection of information, by focus groups we were able to obtain different points of views of the participants such as: Experiences, emotions, testimonies; the semi-structured interview served for the gathering of information from the students and specialists in psychology and sociology; the observation was carried out in public spaces such as streets and public transport showing street sexual harassment; in the quantitative analysis we used the survey which cast precise statistical information related to the topic. Therefore, we determined that the female students are psychologically assaulted in public spaces in the city of Loja, which generates repercussions in the behavior of the victim and increases the invisibility and naturalization of street sexual harassment, also showing oral and non-verbal communication expressed through pick up lines, phrases, lurid gestures, aggressive leering with aggressive sexual content, demonstrating that one of the main causes are the distinct forms of dress of the female that serves to justify machismo and generate gender violence in public spaces, therefore it is necessary to work jointly with the authorities, counselors, parents of families and institutions in charge of the topic and collectives associated with dealing with topics of gender, so that they can be encouraged through campaigns and initiatives which contribute to visualize street sexual harassment, helping to create public spaces with respect and non violence.